Centralized real-time logs investigation in virtual data-center - Vinay, Gatla; Pavan Kumar, T (International Journal of Engineering and Technology, 2018)
Penetration testing is a specialized security auditing methodology where a tester simulates an attack on a secured system. The main theme of this paper itself reflects how one can collect the massive amount of log files which are generated among virtual datacenters in real time which in turn also posses invisible information with excessive organization value. Such testing usually ranges across all aspects concerned to log management across a number of servers among virtual data centers. In fact, Virtualization limits the costs by reducing the need for physical hardware systems. Instead, require high-end hardware for processing. In the real-time scenario, we usually come across multiple logs among VCenter, ESXi, a VM which is very typical for performing manual analysis with a bit more time-consuming. Instead of configuring secure-ids automatically in a Centralized log management server gains a powerful full insight. Along with using accurate search algorithms, fields searching, which includes title, author, and also content comes out of searching, sorting fields, multiple-index search with merged results simultaneously updates files, with joint results grouping automatically configures few plugs among search engine file formats were effective measures in an investigation. Finally, by using the Flexibility Network Security Monitor, Traffic Investigation, offensive detection, Log Recording, Distributed inquiry with full program's ability can export data to a variety of visualization dashboard which exactly needed for Log Investigations across Virtual Data Centers in real time.